2016
DOI: 10.4329/wjr.v8.i11.851
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic positron emission tomography imaging of cancer: Pairing lipid metabolism with glycolysis

Abstract: The limitations of fluorine-18 fluorodeoxy-D-glucose (FDG) in detecting some cancers has prompted a longstanding search for other positron emission tomography (PET) tracers to complement the imaging of glycolysis in oncology, with much attention paid to lipogenesis based on observations that the production of various lipid and lipid-containing compounds is increased in most cancers. Radiolabeled analogs of choline and acetate have now been used as oncologic PET probes for over a decade, showing convincingly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The aim of this study was to evaluate the potential value of 2-[ 18 Grayscale scanning showed that FASN expression in the LNCaP and PC-3 tumors was 33.3% and 10.3% higher than that in the DU145 tumors, respectively. The accumulation (% ID/g) of [ 18 F]FPA in the LNCaP , PC-3 and DU145 tumors decreased by 27.6, 40.5 and 11.7%, respectively, after treatment with orlistat.…”
Section: Abstract Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of this study was to evaluate the potential value of 2-[ 18 Grayscale scanning showed that FASN expression in the LNCaP and PC-3 tumors was 33.3% and 10.3% higher than that in the DU145 tumors, respectively. The accumulation (% ID/g) of [ 18 F]FPA in the LNCaP , PC-3 and DU145 tumors decreased by 27.6, 40.5 and 11.7%, respectively, after treatment with orlistat.…”
Section: Abstract Backgroundmentioning
confidence: 99%
“…Informed consent was obtained before imaging. The patient fasted for at least 6 hours before 18 F-FDG and [ 18 F]FPA was injected intravenously. The start of PET/CT acquisition was 60 min after 18 F-FDG or [ 18 F]FPA injection (3.7 MBq/kg body weight).…”
Section: Patient Preparation and Imaging Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased glucose use by cancer cells is the basis for cancer detection by the uptake of the glucose analogue, fluorine-18-labeled 2-deoxy-2-fluoro-D-glucose ( 18 F-FDG) which can be visualized by positron-emission tomography (PET). PCa cells have a dominant uptake of fatty acid over glucose, alternative tracers have been proposed and PET scanning in PCa is still developing (11). Imaging with PET tracers with 11 C acetate and 11 C choline have shown sufficient sensitivity in the detection not only of primary site, but also of metastasis and recurrence (12).…”
mentioning
confidence: 99%